INOVASI PELAYANAN PUBLIK “HADOHOP VIA DARING” DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KATINGAN SELAMA PANDEMI COVID-19 - Jovano Deivid Oleyver Palenewen (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2022)
This research was conducted at the Department of Population and Civil Registration of Katingan Regency. The purpose of this study was to determine the innovation of Hadohop Via Daring public services at the Katingan Regency Population and Civil Registration Service during the covid-19 pandemic and to determine the inhibiting factors in public service innovation. Qualitative research method with a descriptive approach. Informants in this study are the service and the community who carry out public services for Hadohop Via Daring innovation. The results of this study indicate that the innovation of the Hadohop Via Daring service can be said to be in accordance with the 5 (five) innovation criteria in PERMENPAN-RB No. 3 of 2018 concerning Public Service Innovation Competitions in Ministries/Agencies, Regional Governments, State-Owned Enterprises, and Regional Owned Enterprises, namely: New, Effective, Useful, Transfer Or Replication, And Sustainable. the community. (2). indicators implement the strategy, the Therefore, it can be concluded that the application of Hadohop Via Daring public service innovation has innovation novelty that is effective, beneficial for agencies and the community and innovation is carried out in a sustainable manner. By having 2 (two) inhibiting factors according to Geoff Mulgan & David Albury : Technology exists, but culture and organizational structure are hampered and there is no incentive or reward to increase innovation.